Şamba Balinov'un Haydar Bammat'a gönderdiği yeni yıl tebrik kartı - Balinov, Şamba, 1894-1959 (My University, 1951)
Yeni yıl kutlaması kartı
Keywords: Bammat, Haydar, 1890-1965; Balinov, Şamba, 1894-1959; Munich-Germany